Public personnel reform in Pakistan clashing of ideas - Jones, Garth N. (1994)
The civil service in Pakistan, which was bred in the British imperial tradition, has to grapple with problems confronting Muslim communities such as differences among competing religious groups, racial prejudices and the social caste system. The continuing powerlessness of the poor and the disadvantaged, rampant discourtesy, unsatisfactory public service and elitism count among the major criticisms hurled at the Pakistani bureaucracy. Despite radical efforts to reform the civil service, the establishmentarian personnel system was essentially preserved and even grew stronger. Measures which have been more effective in gradually shaping the civil service have been identified as: (1) maintenance of institutions for public service training; (2) employment of quotas and ethnic preferences; (3) ratioqalization between technocrats and generalists in staffing key positions, (4) provision for lateral appointment and movement of personnel; and (5) establishment of the Unified National Pay Scale.
Keywords: Civil service -- Pakistan; Personnel management -- Pakistan